1996
DOI: 10.1136/adc.74.6.538
|View full text |Cite
|
Sign up to set email alerts
|

Placental weight, birth measurements, and blood pressure at age 8 years.

Abstract: Objective-To examine relationships between blood pressure during childhood and both placental weight and body size at birth, in an Australian population. Design-A follow up study of a birth cohort, undertaken when cohort members were aged 8 years. Setting-Adelaide, South Australia. Subjects-830 children born in the Queen Victoria Hospital in Adelaide, South Australia, during 1975-6. Main outcome measures-Systolic and diastolic blood pressure measured when the children were aged 8 years.Results-Blood pressure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(70 citation statements)
references
References 23 publications
5
62
0
3
Order By: Relevance
“…The increased ratio of placental/fetal weight observed in this study is similar to that described in human IVF pregnancies, where IVF offspring were associated with hypertension later in life (Barker et al 1990, Moore et al 1996, Koudstaal et al 2000. The reasons for the increased ratio of placental/fetal weight are likely complicated; one possible explanation involves a compensatory process for the depressed fetal growth or the impaired function of the placenta itself (Feuer et al 2014, Chen et al 2015.…”
Section: Discussionsupporting
confidence: 68%
“…The increased ratio of placental/fetal weight observed in this study is similar to that described in human IVF pregnancies, where IVF offspring were associated with hypertension later in life (Barker et al 1990, Moore et al 1996, Koudstaal et al 2000. The reasons for the increased ratio of placental/fetal weight are likely complicated; one possible explanation involves a compensatory process for the depressed fetal growth or the impaired function of the placenta itself (Feuer et al 2014, Chen et al 2015.…”
Section: Discussionsupporting
confidence: 68%
“…score. Other studies, but not all, have shown a negative relationship between birth size and blood pressure 23,24 and a positive relationship between birth size and insulin resistance 11 in prepubertal children. This apparent inconsistency could be due to the small number of low weight babies (seven children had a birth weight < 2.50 kg) and the higher mean birth weight (3.47 AE 0.49 kg) in this study compared to others.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with a mean systolic pressure of 150 mm Hg or more, a level sometimes used to define hypertension in clinical practice, comprise a group who as babies were relatively small in relation to the size of their placentas. A rise in blood pressure with increasing placental weight was also found in 4-year-old children in Salisbury, UK, and among 8-yearold children in Adelaide, Australia (37,39). However, in studies of children and adults the association between placental enlargement and raised blood pressure has been inconsistent (40).…”
Section: Possible Mechanismsmentioning
confidence: 96%